2009
DOI: 10.1159/000206856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Neuroimaging and Treatment of Spontaneous Intracranial Hypotension and Magnetic Resonance Imaging Evidence of Blind Epidural Blood Patch

Abstract: Background and Purpose: Spontaneous intracranial hypotension (SIH) is an uncommon, but not rare, cause of headache. We analyzed a series of patients with SIH and attempted to establish a clinical procedure. Methods: We retrospectively reviewed 11 patients with SIH who were admitted between January 2004 and May 2007. Data recorded from patients included basic data, clinical symptoms, neurological imaging studies and treatment. Results: Orthostatic headache was the most common symptom, but there were still 2 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…Long-term relief is thought to be due to formation of dural tamponade that seals the leak (14). Epidural blood patches have been shown to spread within the epidural space over many spinal levels (18), as was shown in the post-procedure CT for our patient.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Long-term relief is thought to be due to formation of dural tamponade that seals the leak (14). Epidural blood patches have been shown to spread within the epidural space over many spinal levels (18), as was shown in the post-procedure CT for our patient.…”
Section: Discussionsupporting
confidence: 57%
“…It involves the injection of autologous blood into the epidural space, and has classically been performed in the lumbar region (14). Many advocate for using EBP without identifying a site of CSF leak (18). The success rate of EBP increases with the volume of blood used, with quotes of 80% success rate with 10-15 cc and >95% success rate with 20 cc of blood (14).…”
Section: Discussionmentioning
confidence: 99%
“…9,29 There are a few reports that observed a minor upward spread of a lumbar blood injection by up to 4 -6 spinal segments. 3,8,29 However, when blood is injected at a site distant from the CSF leak, it is difficult to conceive how the blood can traverse to the desired, remote location, with clotting commencing immediately after injection. Despite some reports of successfully treated CSF leaks with this method, animal experiments have shown that an EBP performed directly at the site of the leak will seal the dural defect more effectively than a blind epidural patch in the lumbar region.…”
Section: Discussionmentioning
confidence: 99%
“…Placing an EBP far from the level of a leak was a possibility, but reported results are mixed. 9,10 Given that this patient was not an ideal operative candidate due to the nonlocalized nature of his leak and previous failed treatment with lumbar EBP, it was thought that a directed approach was reasonable.…”
Section: Discussionmentioning
confidence: 99%